Influences of oak utilization on the medium density fiberboard properties - Osman Çamlıbel; Murat Aydın; Enüs Koç (Maderas: Ciencia y Tecnología, 2024)
Softwoods are the basic and traditional raw materials for medium-density fiberboard production. However, sustainable consumption of wood material in the production of wood-based products requires material variety. Therefore, the usability of hardwood species in the production and its effects on the board properties should be of interest. Considering this, the influence of oak utilization percentages (30 %, 50 %, 70 %, and 100 %) on the physical (density, thickness swelling-TS 2 and 24 h) and mechanical (modulus of rupture, modulus of elasticity, internal bonding, screw holding resistance, and Janka hardness) properties of medium density fiberboard was evaluated in this study. Boards were factory-made instead of laboratory-made using Quercus petraea (oak), Fagus orientalis (beech), and Pinus sylvester (Scots pine) fibers. According to the results, the modulus of rupture, modulus of elasticity, and Janka hardness values were increased when medium-density fiberboard was produced using only oak fiber. On the contrary, thickness swelling, screw-holding resistance, and internal bonding properties were decreased.